Three new species of Simulium (Nevermannia) (Diptera: Simuliidae) from Vietnam - Takaoka, Hiroyuki; Sofian-Azirun, Mohd; Ya’cob, Zubaidah; Chen, Chee Dhang; Lau, Koon Weng; Pham, Xuan Da (Zootaxa, 2014)
Three new species of black flies, Simulium (Nevermannia) langbiangense, S. (N.) phami, and S. (N.) bachmaense, are described on the basis of females, males, pupae and larvae collected in Vietnam. All three species are assigned to the Simulium feuerborni species-group of Simulium (Nevermannia). Simulium (N.) langbiangense sp. nov. is characterized by the female sensory vesicle with a large opening, and a short common basal stalk of the six pupal gill filaments, S. (N.) phami sp. nov. is most striking in having the pupal gill with five filaments, a character not reported in species of the S. feuerborni species-group, and S. (N.) bachmaense sp. nov. is characterized by the female genital fork with a triangular lobe-like projection pointed posteromedially on each arm, and the small larval postgenal cleft. This represents the first record of the S. feuerborni species-group from Vietnam.